Radiology Illustrated: Gastrointestinal Tract - Choi, Byung Ihn (Radiology Illustrated, 2015)
Radiology Illustrated: Gastrointestinal Tract is the second of two volumes designed to provide clear and practical guidance on the diagnostic imaging of abdominal diseases. The book presents approximately 300 cases with 1500 carefully selected and categorized illustrations of gastrointestinal tract diseases, along with key text messages and tables that will help the reader easily to recall the relevant images as an aid to differential diagnosis., Essential points are summarized at the end of each text message to facilitate rapid review and learning. Additionally, brief descriptions of each clinical problem are provided, followed by case studies of both common and uncommon pathologies that illustrate the roles of the different imaging modalities, including ultrasound, radiography, computed tomography, and magnetic resonance imaging.